Community trials on case management of acute respiratory infections (ARI) in rural villages - Cissy B. Kartasasmita; Mintardaningsih Mintardaningsih; O. Rosmayudi; A. U. Suardi; H. Sukandar (Paediatrica Indonesiana, 2001)
A community trial was conducted in two rural subdistricts in Subang, West Java, Indonesia, i.e., Cisalak as the intervention area and Sagalaherang as reference area. The study aimed to evaluate the usefulness new version of case management on acute respiratory tract infections (ARI). All babies born between January and December 1994 were enrolled in the study, and followed for 6 to 12 months. The field workers visited the babies every 2 weeks. They examined the babies and interviewed mothers about ARI symptoms, by using a pretested questionnaire. During that period 969 babies were born, 53.3% in Cisalak and 46.7% in Sagalaherang; 548 of them were followed for 12 months; however, only 263 among them had complete data. The morbidity of ARI increased with increasing age; there was no difference between those two study areas. The prevalence of ARI at the age of less than 3 months was 35.1% and 32.7%; between 4 to 6 months 49.9% and 45.3%; between 7 to 9 months 47.0% and 45.9% ; and between 10 to 12 months 53.7% and 50%, for Cisalak and Sagalaherang, respectively. Nevertheless, the mortality in Sagalaherang was higher than in Cisalak Â (118 per 1000 and 78 per 1000, respectively), and the pneumonia-related deaths were 64.8% and 52.5%, respectively. The age specific death rate for pneumonia was high among babies of less than 3 months of age, i.e., 68.5% and 57.2%, respectively. We conclude that mothers and primary health care workers in rural areas should be taught and encouraged to use case management of ARI, and monitoring and evaluation of the application is needed.